IFN-gamma stimulated dental follicle mesenchymal stem cells regulate activated lymphocyte response in rheumatoid arthritis patients in vitro - DİRESKENELİ, RAFİ HANER; AKKOÇ, TUNÇ (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2019)
Background/aim: Multipotent mesenchymal stem cells (MSCs) have been investigated in autoimmune diseases such as rheumatoid arthritis (RA) due to their immunomodulatory and regenerative properties. In this study, their immunosuppressive effects on peripheral blood mononuclear cells (PBMC) of RA patients were studied. Materials and methods: Dental follicle stem cells (DFSCs) were isolated from follicle tissue in the orofacial region. Characterization and multipotency analyses were performed. Lymphocytes were isolated from peripheral venous blood of RA patients (n 5) and healthy individuals (n = 5). DFSCs were preincubated with IFN-gamma for 48 h. PBMCs of RA patients and healthy individuals were separately cultured with or without DFSCs for 72 h. After culture period, lymphocyte proliferation and viability, the frequency of CD4+CD25(+)FoxP3(+) T regulatory cells, IL-10 and TNF-alpha levels in the culture supernatants were measured via flow cytometry. Results: Our results demonstrated that DFSCs suppressed proliferation of T lymphocytes by increasing the number of FoxP3 expressing CD4(+)CD25(+)T regulatory cells and suppressed lymphocyte apoptosis in RA patients. Also, DFSCs reduced TNF-alpha cytokine secretion and upregulated IL-10 secreting cells. Conclusions: Such cells could potentially be a source for future immunomodulatory treatments of RA patients.
Keywords: Inflammation; mesenchymal stem cells; rheumatoid arthritis; TUMOR-NECROSIS-FACTOR; T-CELLS; THERAPY; TARGET; MECHANISM